Laboratory manual on biological chemistry: for foreign Students of Medical Department of Higher Education institutions : учебное пособие для использования в образовательных учреждениях, реализующих основные профессиональные образовательные программы высшего образования по направлениям подготовки специалитета по специальности 31.05.01 "Лечебное дело" - Байгильдина, А. А. химия Асия Ахметовна (Tutorial, 2019)
The laboratory manual has been written according to the approved curriculum in biological chemistry for students specializing in Medicine. It contains questions for preparing to laboratory and seminar lessons, and description of laboratory tests as well as tests for control knowledge which can be used by students for profound learning of biochemistry.